Pemanfaatan Gim Edukatif “I Can Do” Sebagai Upaya Meningkatkan Literasi Selama Pandemi - Chris Setiawan Adi Putra; Aninditya Sri Nugraheni (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2021)
The weakening level of literacy among schoolchildren has resulted in a slowing of the increase in literacy in Indonesia. The purpose of this research is to find out how effective a person is in utilizing electronic media such as the “I Can Do” game application, especially during the pandemic in order to increase literacy. The method used in this research is descriptive qualitative research which produces a statement that the educational game application "I Can Do" is able to arouse children's enthusiasm for learning, especially during the pandemic period so that the literacy culture that the nation has aspired to approach its main goal.